Colorimetric detection of cholesterol based on highly efficient peroxidase mimetic activity of graphene quantum dots - Nirala N.R.; Abraham S.; Kumar V.; Bansal A.; Srivastava A.; Saxena P.S. (My University, 2025)
In the present study, we report graphene quantum dots (GQDs), an enzyme mimetic of horse radish peroxidase (HRP), for unprecedented detection of free cholesterol. Synthesized directly from graphite using simple and quick one step wet chemical method, these GQDs in the presence of H2O2 exhibit highly efficient catalytic activity toward the oxidation of peroxidase substrate 3,3,5,5-tetramethylbenzidine (TMB) to produce a blue colored product. The proposed detection system based on GQDs allows wide range (0.02-0.6 mM) of cholesterol sensing with a detection limit as low as 0.006 mM. Further, higher Vmax (7.3 × 10-6 M s-1) along with lower Km (0.01 mM) attest enhanced peroxidase like catalytic activity and better binding affinity of cholesterol oxidase (ChOx) to cholesterol resulting in good biosensor stability and resistance to environmental interferences. The proposed method without the use of sophisticated instruments perceives the cholesterol using naked eye with blue color compound formation. The potential of the method to be applied on field is shown by the proposed cholesterol measuring color wheel, where the shades of color are related to actual levels of cholesterol in the sample. © 2015 Published by Elsevier B.V.